Pengaruh Brand Association, Nutrition Label, dan Trust Terhadap Perilaku Pasca Pembelian Produk Cimory Yogurt - Okky Pramudya Wardana; Mintarti Indartini; Ahadiati Rohmatiah (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the partial and simultaneous influence of brand association, nutrition labels, and trust on the post-purchase behavior of Cimory Yogurt products in the Ngawi District. This type of research is quantitative, with primary data sources covering a sample of 384 respondents. Data was collected through questionnaires and analyzed using multiple linear regression, with data analysis techniques including the t-test, F-test, and the coefficient of determination (R²). The results of the study indicate that partially, brand association, nutrition labels, and trust each have a positive and significant influence on the post-purchase behavior of Cimory Yogurt products in the Ngawi District. Simultaneously, these three variables are also proven to have a significant influence on the post-purchase behavior of Cimory Yogurt products in Ngawi District. These findings indicate that positive brand associations, clear nutritional information, and consumer trust are key factors driving loyalty and repeat purchases.